Kommunicera, relatera eller provocera? - Arvidsson,Elsa; Jönsson,Leia; Olnäs,Leonora (2025)
Research question: How do young adults perceive a norm-breaking tone of voice from brands on social media? Purpose: The purpose of the study is to understand how the communication is perceived, what reactions it evokes from young adults, as well as what consequences it has for consumption and brand image. Methodology: A qualitative method in the form of semi-structured interviews with young adults (ages 18-25), complemented by selected posts from Duolingo’s and Ryanair’s official TikTok and Instagram platforms. Theories: The study is based on four theoretical perspectives that together shed light on how brand communication functions and influences consumers. The theories are The Dangers of Common Sense, Customer-Based Brand Equity Model, How Humor in Advertising Works & Watch Your Tone. Together, these frameworks offer a multifaceted understanding of how tone of voice and emotional elements in digital communication can contribute to stronger brand engagement. Analysis: The collected material was thematically structured into three overarching categories: positive, ironic and engaging factors. These served as analytical frameworks to clarify how young adults perceive and relate to a norm-breaking tone in brand communication. Within these categories a total of nine sub-themes were identified, formulated based on common perceptions expressed by the respondents. Conclusion: The study shows that young adults generally appreciate and are more likely to engage with brands that have a norm-breaking tone in corporate communication on social media, provided it is perceived as genuine and aligned with the brand’s identity. At the same time the findings reveal that recipients are critical and sensitive to exaggerated or inauthentic messaging. The effect of tone is therefore context-dependent and must be adapted to the brand’s identity to be perceived as credible and engaging. It is not only about what is said, but very much about who says it and how it is said.
Keywords: Normbrytande tonalitet; Sociala medier; Varumärkeskommunikation; Humor; Sarkasm; Trend; Autenticitet; Unga vuxna; Duolingo; Ryanair; Digital marknadsföring